Subacute thyroiditis following seasonal influenza vaccination. Issue 4 (2nd April 2016) - Altay, Fatma Aybala; Güz, Galip; Altay, Mustafa
Abstract: A peritoneal dialysis patient who experienced a repeating attack after a vaccination for influenza while she was being followed and treated succesfully for subacute thyroiditis (SAT) is presented. This case shows SAT as a rare condition following vaccination.. Thus, SAT should be considered as a possible outcome following influenza vaccination and flu-like syndrome.